2021
DOI: 10.4037/ajcc2021178
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Injuries Due to Personal Protective Equipment in COVID-19 Critical Care Units

Abstract: Background Caring for patients with COVID-19 requires wearing a full set of personal protective equipment (PPE) to avoid contamination. Personal discomfort has been associated with use of PPE, and anecdotal reports describe pressure injuries related to wearing PPE. Objectives To investigate the occurrence of device-related pressure injuries due to wearing PPE among Italian nurses caring for patients with COVID-19 in critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 13 publications
(22 reference statements)
2
25
0
3
Order By: Relevance
“…The NPIAP acknowledged the need for prophylactic measures to mitigate pressure injuries secondary to PPE use. 20 However, they also reported the uncertainty of utilising dressings under PPE due to the risk of seal integrity. 21 Therefore, our study protocol included standardised fit testing, before and after, application of the tested dressings, as a secondary aim and additional safety element.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPIAP acknowledged the need for prophylactic measures to mitigate pressure injuries secondary to PPE use. 20 However, they also reported the uncertainty of utilising dressings under PPE due to the risk of seal integrity. 21 Therefore, our study protocol included standardised fit testing, before and after, application of the tested dressings, as a secondary aim and additional safety element.…”
Section: Discussionmentioning
confidence: 99%
“…As the pandemic evolved and higher incidence of facial skin injury was noted with long‐term PPE wear. The NPIAP acknowledged the need for prophylactic measures to mitigate pressure injuries secondary to PPE use 20 . However, they also reported the uncertainty of utilising dressings under PPE due to the risk of seal integrity 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência de lesão por pressão foi bastante elevada entre os médicos (59,2%), porém inferior a outros estudos recentes. (Coelho et al, 2020;Bambi et al, 2021). observou-se que os indivíduos que utilizaram a máscara N95 em associação aos óculos de proteção e apresentaram sudorese tiveram um risco muito elevado de desenvolver lesões.…”
Section: Discussionunclassified
“…According to Bambi et al, PPE-related FPI developed in 77.1% of nurses who worked in intensive care in the COVID-19 pandemic period [ 14 ]. The results of our study revealed the risk of FPI development in the participants who worked in intensive care to be 1.8 times as high as the risk of others.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the prolonged use of PPE may result in various dermatoses, including the exacerbation of previously existing skin disorders such as facial pressure injuries (FPI), contact dermatitis, pressure urticaria, seborrheic dermatitis, and acne [ 4 , 11 , 13 ]. It has been frequently observed that especially in healthcare workers, pressure injuries develop in the face after the prolonged use of facemasks and face-protective equipment [ 14 ]. When PPE is used, especially throughout an entire working shift that can last as long as 12 h, it will create constant pressure, friction, and abrasion on the skin it has contact with.…”
Section: Introductionmentioning
confidence: 99%